Integrasi Ilmu dan Agama dalam Perspektif Filsafat Pendidikan Islam - Khoerunnisa Nidaul Khusna; Novita Amalia; Tsabit Damawi Ikhsan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The integration of science and religion from the perspective of Islamic educational philosophy is an effort to unite general knowledge and religious values into a unified whole. To date, the dichotomy between science and religion has often created inequalities in the education system, both conceptually and practically. Through an Islamic educational philosophy approach, this integration aims to shape individuals who are not only intellectually intelligent but also possess spiritual depth and noble morals. This concept emphasizes that all knowledge essentially originates from God and must be used for the benefit of humanity. Thus, Islamic education is expected to produce a generation that balances faith, knowledge, and good deeds in their daily lives.